ADOPTION INSIGHTS: EXPLORING CONSTRUCTS IN TECHNOLOGY ACCEPTANCE THEORIES - Azliza Yacob; Noraida Hj Ali; Aimi Dalila Roslim; Noor Suhana Sulaiman; Nur Sukinah Aziz; Azlin Ramli, (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2025)
The rapid evolution of technology necessitates a deeper understanding of the constructs influencing its adoption across various sectors. This systematic literature review examines the common constructs and suggest new constructs to be use within technology adoption theories to enhance understanding of user acceptance. The primary problem is the need an updated and structured review to identify the common construct use within the technology adoptions theory and suggest new constructs that is consider uncommon to be used for paper. To achieve this, we conduct a detailed search approach is implemented, applying specific keywords and criteria to reputable databases such as Scopus and Web of Science. The flow of research is based on PRISMA framework. The research targeted studies published from 2022 to 2024, resulting in the analysis of 45 primary data entries. The finding was divided into three themes which is (1) user acceptance and behavioural intentions, (2) technology integration and innovation and (3) sustainability and social impact. The analysis revealed among the 44 constructs analysed, only three are deemed common. These constructs are Trust, Security Risk, and Attitude. In conclusion, the constructs identified in this study form a foundational basis for further research and development of technology adoption theories, underlining the importance of ongoing research into their implications while also considering studying constructs that are outside of Computer Science subject.